Potential of Astaxanthin from Asian Tiger Shrimp (Penaeus Monodon) Shell Extract as an Antibacterial and Ant Inflamatory - Sukmawati . (Journal of Global Pharma Technology, 2016)
Asian tiger shrimp (Penaeus monodon) shell is an industrial waste which becomes one of the sources of carotenoids in the form of astaxanthin (3.3’-dihydroxy-β, β′-carotene-4.4′-dione) which has a very potential biological activity because it can work on target molecules. Astaxanthin in Asian tiger shrimp shell is well known to be lipophilic, being insoluble in water but soluble in organic solvents, one of which acetonitrile. The characteristics of astaxanthin were obtained through qualitative and quantitative analyses using FTIR (Fourier Transform Infra-Red) and HPLC (High Performance Liquid Chromatography). Furthermore, antibacterial and anti-inflammatory activities had been tested. Based on the research results done on the inhibition of Asian tiger shrimp (Penaeus monodon ) shell extract on the 5th growth of the test bacteria, the tiger shrimp shell extract had antibacterial activity on Eschericia coli., Streptococcus mutans, Pseudomans auriginosa, Salmonella typhi, Staphylococcus aureus which was characterized by the presence of clear zone / inhibition zone / Oligodynamic zone which showed the effect of tiger shrimp shell extract in killing and inhibiting the growth of test bacteria. Besides, An anti-inflammatory testing through extracting chemical components with acetonitrile solvent with several concentrations showed that the anti-inflammatory activity with a concentration of 1000 ppm with % stability on erythrocyte membrane obtained 60.516%, indicating that the higher the concentration used, the better was the anti-inflammatory effect.Keywords: Astaxanthin, Asian tiger shrimp, Antibacterial, Anti-inflammatory.